Determining the Predominant Governing Parameters of the Bed-Load Equations for Sediment-Laden Rivers on the Continental Shelf - Khorram, S.; Ergil, M. (Journal of coastal research, 2011)
Sediment transport between the emerged land masses and deep marine basins is a fundamental process that affects the exploitation of resources and protection of the environment and its ecosystems. Sediment transport models on the continental shelf are often very complex and subject to semiempirical or empirical equilibrium transport equations that relate sediment fluxes and turbulence to physical properties such as velocity, depth, and characteristic bed-load sediment particle sizes. In engineering applications, errors in these physical properties affect the accuracy of the sediment fluxes. The present analysis details the importance of physical properties to the bed-load fluxes and suggests which parameters have more influence on the final result by providing insight into the relative strengths, weaknesses, and limitations of all the selected 52 bed-load equations for noncohesive particles (sand and gravel are treated separately). Various parameters were first investigated individually to pinpoint the key physical properties that control the errors. Because the existence of strong nonlinearity in most bed-load transport equations precludes analytical approaches, the multilinear regression (MLR) method was used to validate this analysis. Several graphs are presented to emphasize the influencing effect of those parameters that were either used directly or embedded in these equations. The most significant parameters that directly influence the sand particles are θ, ds, and vav, and the embedded parameters are sfτo, θds, and Sfθ. On the other hand, for gravel particles, the most significant parameters are θ, ds, and θcr and qs*, Sfθ, and sfτo, respectively.